PENILAIAN MAHKAMAH KONSTITUSI TERHADAP CABANG PRODUKSI YANG DIKUASAI OLEH NEGARA: Penilaian Mahkamah Konstitusi terhadap Cabang Produksi yang Dikuasai oleh Negara - Fitriyani, Desi (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The state controls production branches that are important to the state and/or affect the livelihood of the people at large. Regarding the evaluation, it is in the hands of the Government together with the Parliament. Problems then arise, when there are no indicators to carry out this assessment, leading to abuse of power and the privatization, injuring the right to control the state. On that basis, the Constitutional Court was present to conduct an assessment of the Government's assessment with the Parliament. This study aims to determine the Constitutional Court's role in carrying out this assessment. This research is normative legal research. Results of the study show that the Constitutional Court has exercised this authority by providing its judgment by reviewing the law. In the future, the Constitutional Court must issue indicators of branches of production controlled by the state based on Article 33 of UUD NRI 1945.